A Capable Smart Sensor Interface Module for Interoperable Ocean Observatories. (July 2018) - Lin, Shijun; Lyu, Feng
Abstract: The rapid development of ocean observatories results in a great challenge to integrate so many sensors into one system. Some solutions have been proposed to address this issue, such as MBARI PUCK, IEEE 1451 and OGC SWE. This paper proposes a novel smart sensor interface module solution which is more capable than PUCK. As the interface standardization is achieved at the instrument-side in our solution, the design of ocean observatory systems is simplified. What's more, the feature of distributed intelligence of the module can benefit many in-situ applications of ocean observatories.